Bogging down investors: An unintended consequence of litigation risk - FU, Siwen (Institutional Knowledge at Singapore Management University, 2025)
Securities litigation risk is a well-recognized yet underexplored source of financial reporting complexity or unreadability. This study examines the effect of litigation risk on the readability of corporate financial reports. The 1999 Silicon Graphics Inc. (SGI) court ruling unexpectedly reduced litigation risk for firms within the Ninth Circuit Court’s jurisdiction. Using a difference-in-differences design centered on the SGI court ruling, we find that, while the readability of financial reports generally declines over the sample period, treated firms in the Ninth Circuit experience a comparatively smaller decline in readability than control firms in other states after the ruling. Put differently, treated firms experience a relative improvement in reporting readability following the ruling. This effect is concentrated among firms prone to securities litigation and those with greater external financing needs, but it is muted for firms engaging in earnings management. Furthermore, improved reporting readability among treated firms can be partially attributed to alleviated concerns about the adequacy of cautionary language, as evidenced by a significant decrease in negative forward-looking statements, particularly risk-related ones. Collectively, our findings suggest that securities litigation risk contributes to reduced readability in financial reporting.